Biobanking strategy and sample preprocessing for integrative research in monoclonal gammopathies - Ševčíková, T; Growková, K; Kufová, Z; Filipová, J; Vrublová, P; Jelínek, T; Kořístek, Z; Kryukov, F; Kryukova, E; Hájek, R (Journal of clinical pathology, 2017)
AIMS: Some types of monoclonal gammopathies are typified by a very limited availability of aberrant cells. Modern research use high throughput technologies and an integrated approach for detailed characterisation of abnormal cells. This strategy requires relatively high amounts of starting material which cannot be obtained from every diagnosis without causing inconvenience to the patient. The aim of this methodological paper is to reflect our long experience with laboratory work and describe the best protocols for sample collection, sorting and further preprocessing in terms of the available number of cells and intended downstream application in monoclonal gammopathies research. Potential pitfalls are also discussed. METHODS: Comparison and optimisation of freezing and sorting protocols for plasma cells in monoclonal gammopathies, followed by testing of various nucleic acid isolation and amplification techniques to establish a guideline for sample processing in haemato-oncology research. RESULTS: We show the average numbers of aberrant cells that can be obtained from various monoclonal gammopathies (monoclonal gammopathy of undetermined significance/light chain amyloidosis/multiple myeloma (MM)/MM circulating plasma cells/ minimal residual disease MM-10 123/22 846/305 501/68 641/4000 aberrant plasma cells of 48/30/10/16/37×106 bone marrow mononuclear cells) and the expected yield of nucleic acids provided from multiple isolation kits (DNA/RNA yield from 1 to 200×103 cells was 2.14-427/0.12-123 ng). CONCLUSIONS: Tested kits for parallel isolation deliver outputs comparable with kits specialised for just one type of molecule. We also present our positive experience with the whole genome amplification method, which can serve as a very powerful tool to gain complex information from a very small cell population.
Keywords: Paraproteinemias; Cryopreservation; Blood Preservation; reagenční diagnostické soupravy; Blood Specimen Collection; METHODOLOGY; DNA; lidé; krevní bankovnictví; RNA; konzervace krve; kryoprezervace; HAEMATO-ONCOLOGY; odběr vzorku krve; paraproteinemie; MYELOMA; Blood Banking; Reagent Kits, Diagnostic; Humans